What are the determinants of financial well‐being? A Bayesian LASSO approach. - Lacombe, Donald J.; Khatun, Nasima (American Journal of Economics & Sociology, 2023)
The financial well‐being (FWB) of individuals is a topic that is becoming increasingly important across a multitude of disciplines. In this study, we use the 2016 National Financial Well‐Being Survey administered by the Consumer Financial Protection Bureau to assess the determinants of an individual's FWB. We identify 144 potential covariates that could explain variation in the FWB score of individuals. The statistical methodology of choice is the Bayesian LASSO, which is a covariate selection algorithm that also allows for the importance ranking of covariates. Out of the 144 potential covariates, we find that 26 have 95% credible intervals that do not contain zero. Broadly speaking, the results show that objective measures of financial competency and psychological and sociological factors contribute the bulk of the explanatory power that help explain an individual's FWB score.